Prevalence of pneumonia and associated factors among children aged 6–59 months in Angolela Tera district, North Shoa, Ethiopia, 2021, community-based cross-sectional study - Leweyehu Alemaw Mengstie (Bulletin of the National Research Centre, 2022)
Abstract Background Childhood pneumonia is the commonest cause of suffering worldwide. Among under-five children where it accounts for more than one out of seven under-five death globally. It is the single leading cause of death in Ethiopia, accounting for 18% of all under-five mortality burdens. These deaths are easily preventable and treatable through simple and cost-effective interventions. The study aims to assess the prevalence and associated factors of pneumonia among under-five children at Angolela Tera district, North Shoa, Ethiopia, 2021. A community-based cross-sectional study was conducted on a simple random sample with a sample size of 414 registered mothers with 6–59 months of children. Semi-structured questionnaires were used to collect data. The data were entered using the EpiData version 3.1, and analysis was done by SPSS version 24. Bivariable and multivariable logistic regression analysis was used. Results The prevalence of pneumonia in children under five was 5.8% (95% CI 3.6–8.2%). Based on the multivariable logistic regression analysis of this study, child male sex, have no family toilet, children having fever in the last 2 weeks, lack of maternal ANC follow-up and children with stunted were associated with pneumonia. Conclusions The study shows that the prevalence of under-five pneumonia was low as compared to recent EDHS 2016. Therefore, by making interventions on potential determinates such as by improving family latrine utilization, improving the nutritional status of children, and early control of respiratory tract infection and fever, we can reduce under-five pneumonia.